Green Room – An architectural and urban device for energy efficiency and environmental comfort - Luigi Coccia; Sara Cipolletti; Gianmarco Corvaro (Agathón)
The article presents a design experiment conducted within the research PNRR VITALITY based on the issues of sustainability and the quality of living spaces. Considering the innovation opportunities expressed by the energy transition, also achieved through nature-based regenerative solutions, aimed at reducing consumption and CO2 emissions, the methodology leads to the conceptualisation of the multiscalar spatial device Green Room: a volumetric decrement action associated with vegetative infiltration applied to significant parts of buildings and open spaces in three sample areas of the Adriatic-Mediterranean region. Starting from morphological, typological, and climatic data and managing computational simulation processes, the experiment aims to update design tools at the architectural and urban scale, establishing a relationship between indoor and outdoor spaces to achieve benefits for the environment and people’s well-being.